Human Resource Management in Improving the Performance of Religious Education Tourism Managers in Loning Purworejo Village - Aziz, Abdul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The existence of the Tuan Guru Tomb and the Loning Mosque to become religious educational tourism is very important and has the potential to be developed. However, managers have not been able to carry out the development of these tourist attractions properly due to a lack of knowledge of resource management. This study aims to analyze the performance problems of managing religious education tourism in Loning Village, Kemiri District, Purworejo Regency. This was done for 45 days in Loning Village. This study uses qualitative methods with data collection techniques of observation, interviews and documentation. The collected data is tested by the settlement method when collecting data. The results of this study indicate that human resource management (HR) assistance can help overcome the problems of managing religious educational tourism at the Tuan Guru Loning Tomb and Mosque in Loning Village. Managers of religious education tourism in Loning Village can understand and implement optimal and optimal management of the resources incorporated in it.